ANALISIS KEPATUHAN PAJAK PENGHASILAN PASAL 23 ATAS JASA KONSULTAN PADA PT. PERKEBUNAN NUSANTARA IV - -, Amelia; -, Junawan; Syauqi, Teuku Radhifan (JURNAL PERPAJAKAN, 2024)
Income Tax is a tax imposed on modular income, services, gifts and awards, other than those withheld by Article 21 Income Tax. This study was conducted with the aim of determining the suitability of fulfilling Article 23 Income Tax for consulting services at PT. Nusantara Plantation IV. The data analysis technique used in this research is descriptive qualitative. The results of this study indicate that the withholding of Article 23 Income Tax by PT. Perkebunan Nusantara IV has complied with Law Number 36 of 2008 concerning Income Tax. However, there was a delay in depositing Income Tax Article 23 that occurred in March and December 2020 due to a system error when making the deposit.